2000
DOI: 10.1002/1099-0844(200009)18:3<169::aid-cbf870>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and lipid peroxidation status in the blood of patients with alopecia

Abstract: The aim of this research was to determine levels in blood of vitamin E, beta-carotene, lipid peroxidation as thiobarbituric-acid reactive substances (TBARS) and reduced glutathione (GSH) and activity of glutathione peroxidase (GSH-Px) in patients with alopecia. Studies were carried out on 37 patients with alopecia and 34 healthy age-matched controls. Red blood cell (RBC) and plasma samples from healthy and patient subjects were taken. Beta-cartotene levels (P<0. 001) in plasma and levels of GSH (P>0.05) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 17 publications
3
33
0
7
Order By: Relevance
“…Some studies have suggested the use of antioxidants as supplements for the treatment of AA based on these evidences. 5,13 Few human-and animal-based studies have demonstrated enhanced hair growth as a result of antioxidant use. 28,29 We think that properly conducted interventional studies are required to elucidate the role of antioxidants in the management of AA patients.…”
Section: Association Between Aa and Oxidative Damage Products/ Oxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested the use of antioxidants as supplements for the treatment of AA based on these evidences. 5,13 Few human-and animal-based studies have demonstrated enhanced hair growth as a result of antioxidant use. 28,29 We think that properly conducted interventional studies are required to elucidate the role of antioxidants in the management of AA patients.…”
Section: Association Between Aa and Oxidative Damage Products/ Oxidantsmentioning
confidence: 99%
“…4 Several studies have investigated the levels of oxidative stress markers, antioxidants, and oxidative damage products in plasma, erythrocytes, and scalp tissues of AA patients. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] We conducted this systematic review and meta-analysis to investigate the association between AA and oxidative stress and to clarify the inconsistent findings across previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E is another nutrient involved in the oxidant/antioxidant pathway, serving an instrumental role in defense against free-radical damage to the plasma membrane [89]. Investigators in Egypt assessed serum and tissue vitamin E levels in 15 patients with AA, finding lower levels in cases compared to healthy controls [90].…”
Section: Micronutrientsmentioning
confidence: 99%
“…Investigators in Egypt assessed serum and tissue vitamin E levels in 15 patients with AA, finding lower levels in cases compared to healthy controls [90]. In contrast, investigators from Turkey found no differences in vitamin E levels, but did identify lower levels of beta-carotene in AA cases vs. controls [89]. Beta-carotene is a precursor to vitamin A and an antioxidant [63].…”
Section: Micronutrientsmentioning
confidence: 99%
“…Few studies have recently proposed the role of oxidative stress in AA. [6][7][8] Oxidative stress is a condition of oxidant ⁄ antioxidant disequilibrium, in which increased reactive oxygen species (ROS) generation overwhelms antioxidant defence mechanisms leading to oxidative damage of cellular molecules. Of these, lipids are the most sensitive in that polyunsaturated fatty acids in cell membrane react with free radicals to form peroxidation products.…”
Section: Introductionmentioning
confidence: 99%